Deterinination of toxoplasma gondii seroprevalenee by indireel fluoreseent antibody (lfa) test in abortion experieneed and abortion inexperieneed sheep in karapınar distriel of konya - Mehmet Aköz; İbrahim Aydın; Kadir Kamburgil (Eurasian Journal of Veterinary Sciences)
The objective of this study was to determine Toxoplasma gondii seroprevalence by Indirect Fluorescent Antibody (lFA) Test in abortion experienced and abortion inexperienced sheep in Karapınar district of Konya. For this purpose, total 184 sheep,106 abortion experienced and 78 abortion inexperienced, were examined. Blood samples were collected from sheep and sera were separated. Serum samples were examined for the presence of anti-Toxoplasma gondii antibodies by lFA test. Reactions at titers of 1/64 and more were accepted positive. T. gondii antibodies were detected in 24 (13%) of total 184 sheep, 12 (11.3%) of 106 abortion experienced and 12 (15.4%) of 78 abortion inexperienced sheep. There was no significant difference between abortion experienced and abortion inexperienced sheep in respect to detected seroprevalence (P>0.05). Antibody titers were determined from 1/64 to 1/2048 in the study. There was no significant difference between seroprevalence and age in abortion experienced and abortion inexperienced sheep (P>0.05). Determined sereprevalence values are not despised level in abortion experience d and abortion inexperienced sheep because of economic and zoonoses importance of Toxoplasmosis. Seroprevalence resarehes should be done for keep under the control of Toxoplasmosis in sheep.